Structure and Psychometric Properties of Job Satisfaction Scale for a Sample of Secondary School Teachers in Gaza - Ahmed Omar, Mahmoud; Ali AlJerrgaw, Ziad; Ahmed Ali Haiba, Mohamed; Ahmed Al-Basiony, Maysa (International Journal of Psychosocial Rehabilitation, 2020)
The present study attempts to examine the structure and psychometric properties of the job satisfaction scale for a sample of secondary school teachers in Gaza. The study questions addressed are: What is the structure of the measure of job satisfaction for secondary school teachers in Gaza? Does the job satisfaction scale have appropriate psychometric properties? A total of 205 teachers from Gaza completed the scale of job satisfaction, including males (N= 121) and females (N= 84). The teachers ranged in age from 30 to 48, with an average age of 38.87 and an S.D. of 10.1. Exploratory factor analysis (EFA) is used. The results indicate that the structure of job satisfaction is multidimensional, which includes salary, school environment conditions and the nature of work, and supervision, and the scale has appropriate psychometric properties.